2015
DOI: 10.1016/j.bbapap.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of monomer arrangement in the amyloid self-assembly

Abstract: Assembly of amyloid proteins into aggregates requires the ordering of the monomers in oligomers and especially in such highly organized structures as fibrils. This ordering is accompanied by structural transitions leading to the formation of ordered β-structural motifs in proteins and peptides lacking secondary structures. To characterize the effect of the monomers arrangements on the aggregation process at various stages, we performed comparative studies of the yeast prion protein Sup35 heptapeptide (GNNQQNY)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
(65 reference statements)
3
19
0
Order By: Relevance
“…1b ) like those observed for full size Aβ proteins, the presence of non-native species can produce vastly different morphologies. The hairpin peptide forms globular features, like those for GNNQQNY peptide 30 , with no evidence of the formation of fibrils or protofibrils (Fig. 1c ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…1b ) like those observed for full size Aβ proteins, the presence of non-native species can produce vastly different morphologies. The hairpin peptide forms globular features, like those for GNNQQNY peptide 30 , with no evidence of the formation of fibrils or protofibrils (Fig. 1c ).…”
Section: Resultsmentioning
confidence: 95%
“…30. Briefly, AFM probes (MSNL, Bruker, CA) were cleaned with ethanol and water, followed by treatment with UV (λ 366 nm) light for 45 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The force curve was approximated with the worm like chain (WLC) model, 34 and the rupture force value was calculated from this approximation. 18, 35 Experiments were performed at pH 7 and pH 3.7, and several hundred force curves were assembled into histograms for each pH value.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Growth of amyloids occurs by the nucleated polymerization of soluble proteins of a particular sequence. 3,4 Many proteins can polymerize to form amyloid when provided an appropriate environment in vitro, indicating this as inherent characteristic of polypeptides. Indeed, many recent studies have shown the existence of beneficial amyloids that are important for survival of a host organism.…”
Section: Introductionmentioning
confidence: 99%